The requirement for endothelial cell tetrahydrobiopterin in health and disease - Chuaiphichai, S (2014)
Tetrahydrobiopterin (BH4) is an essential cofactor for endothelial nitric oxide synthase (eNOS) function and nitric oxide (NO) generation. Augmentation of BH4 levels can prevent eNOS uncoupling and improve endothelial dysfunction in vascular disease states. However, the physiological requirement for de-novo endothelial cell BH4 biosynthesis in eNOS function remains unclear. We generated a novel mouse model with endothelial cell-specific deletion of GCH1, encoding GTP cyclohydrolase 1, an essential enzyme for BH4 biosynthesis, to test the cell-autonomous requirement for endothelial BH4 biosynthesis under physiological conditions and disease states in vivo. Mice with a floxed GCH1 allele (GCH1fl/fl) were crossed with Tie2cre mice to delete GCH1 in endothelial cells. GCH1fl/flTie2cre mice demonstrated reduced NO bioactivity and significantly greater O2•- production. GCH1fl/flTie2cre aortas and mesenteric arteries had impaired endothelium-dependent vasodilatations to acetylcholine. Endothelium-dependent vasodilatations in GCH1fl/flTie2cre aortas were in part mediated by NOS-derived hydrogen peroxide, through soluble guanylate cyclase. GCH1fl/flTie2cre mice had higher systemic blood pressure than wild-type littermates, which was normalised by the NOS inhibitor, L-NAME. In a lipopolysaccharide (LPS)-induced systemic inflammation model, GCH1fl/flTie2cre mice were partially protected against LPS-induced vascular dysfunction and hypotension compared to wild-type littermates. In the angiotensin II (Ang-II)-induced hypertension model, chronic Ang II infusion with a sub-pressor dose caused hypertension in GCH1fl/flTie2cre mice but did not alter blood pressure in wild-type littermates. Abdominal aortic aneurysms (AAA) in response to Ang II infusion were observed in GCH1fl/flTie2cre but not in wild-type mice. In pregnancy, GCH1fl/flTie2cre mice exhibited a loss of NOS-derived NO mediated vasodilatation, impaired uterine vascular adaptation, increased blood pressure and fetal growth restriction. Taken together, these studies reveal that endothelial cell GCH1 and BH4 biosynthesis play a pivotal role in vascular function and blood pressure regulation in health and disease. Therefore, targeting vascular GCH1 and BH4 biosynthesis may provide a novel therapeutic target for the prevention and treatment of vascular dysfunction in patients with hypertension, AAA formation, septic shock and preeclampsia.